Solo : a star wars story [videorecording (DVD)] - Howard, Ron, 1954-; Ehrenreich, Alden, 1989-; Harrelson, Woody; Clarke, Emilia, 1986- (Buena Vista Home Entertainment, 2018)
Follows young Han Solo through a series of daring escapades in a dangerous criminal underworld, where he meets his future co-pilot, Chewbacca, and the notorious gambler Lando Calrissian.